2011
DOI: 10.1038/ncomms1525
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale DNA editing of retrotransposons accelerates mammalian genome evolution

Abstract: Retrotransposons had an important role in genome evolution, including the formation of new genes and promoters and the rewiring of gene networks. However, it is unclear how such a repertoire of functions emerged from a relatively limited number of source sequences. Here we show that DnA editing, an antiviral mechanism, accelerated the evolution of mammalian genomes by large-scale modification of their retrotransposon sequences. We find numerous pairs of retrotransposons containing long clusters of G-to-A mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
54
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 50 publications
3
54
0
1
Order By: Relevance
“…DNA and RNA editing of retroelements enhances intra-and interspecies diversity. We screened the BMR genome and transcriptome for these, making BMR one of the first organisms to be comprehensively analysed for both types of editing, preceded only by human and mouse 51 .…”
Section: Resultsmentioning
confidence: 99%
“…DNA and RNA editing of retroelements enhances intra-and interspecies diversity. We screened the BMR genome and transcriptome for these, making BMR one of the first organisms to be comprehensively analysed for both types of editing, preceded only by human and mouse 51 .…”
Section: Resultsmentioning
confidence: 99%
“…Experiments have shown that the APOBEC3 family can actively inhibit retrotransposition of LTR retroelements in yeasts, mice, and humans (42, 61-63, 77, 78), but whether the LTR elements have evolved or become inactivated from mutations by APOBEC3s is unclear. What is known so far is that a few HERV-K sequences contain the footprint of the G-to-A mutation induced by hA3G only (79). Interestingly, in a recent communication by Carmi et al (79), pairwise comparison of retroelement genomes has identified sequences with clusters of Gto-A mutations that have been attributed by the authors to the APOBEC3 enzymes.…”
Section: Figmentioning
confidence: 99%
“…Because sharply divergent geological, edaphic, climatic, and biotic interfaces abound in nature, we conclude that SS may be a common model of the origin of new species, as envisaged by Darwin. during reverse transcription (among other mechanisms). In some cases, DNA-edited elements successfully enter the genome despite being hypermutated, containing a series of G-to-A mutations (15,16). These sequences enhance genomic diversity and, therefore, increase the potential of developing new traits.…”
mentioning
confidence: 99%